Aloran Water Level Monitoring System with Web Data Logging Utilizing Ultrasonic Sensor - Amin, Warnner Daminar; Salaguste, Gail Diane; Gabayan, Charlyn M; Pereno, Allene S.; Caw-it, Jelly Grace A. (Universitas Multi Data Palembang, 2025)
The Aloran Water Level Monitoring System was developed to enhance disaster preparedness by integrating real-time monitoring, data logging, and warning mechanisms. Utilizing ultrasonic sensors, Arduino UNO R3, and ESP8266 microcontrollers, the system measured water levels and transmitted data to a local web server. A GSM module sent real-time alerts, while warning lights activated at critical thresholds. Testing confirmed high accuracy in water level measurement, effective real-time data logging, and timely notifications, earning a 4.42 general weighted mean (“Very Good”). The system proved reliable and cost-effective for flood monitoring and disaster risk reduction. Recommendations include incorporating solar-powered modules for remote deployment, cloud-based servers for broader accessibility, and predictive analytics for improved flood forecasting.